Medicinal ethnobotanical knowledge across urban cultural groups: A case study in a South African township - Prinsloo, Kara - Lee; Kleynhans, Riana; Jansen, Ray (Ethnobotany Research and Applications, 2023)
Background: The use of medicinal plants for primary health care is still prevalent in southern Africa, but the decline in indigenous traditional knowledge is cause for concern as this could lead to a loss of valuable indigenous cultural knowledge. Many ethnobotanical studies have been conducted amongst rural communities, however limited information is available on the indigenous cultural knowledge amongst mixed tribal urban communities Methods: This study was conducted in the diverse urban township of Tembisa, located in the eastern parts of Gauteng Province in South Africa. Through the use of structured questionnaires (n=2724), the Zulu, Tsonga, and Pedi ethnic groups' knowledge of 17 regularly used medicinal herbs was assessed. Results: Our findings indicated that indigenous traditional knowledge is still prevalent in this urban setting, although the extent of this knowledge was significantly influenced by cultural group, participant age, residency period and age of migration into this urban environment. Two plant species Artemisia afra and Helichrysum odoratissimum, were particularly well known amongst all cultural groups, but knowledge on other plants varied. Generally, the younger generation had less knowledge than the elders with the exception for the Tsonga people. Conclusion: Although it was refreshing to find that cultural knowledge about medicinal plants still exists in an urban environment, the perceived lack of knowledge among the younger generation can be viewed as a risk to the continued existence of this knowledge, especiaaly if the opportunities to relay this knowledge becomes less, as influenced by modern urban living. Keywords: ethnobotany, medicinal plants, cultural knowledge, urban environment